Efectos del cambio al horario de verano en la salud mental de los adolescentes: una revisión - González G., Carlos; Torres Q., Claudio (Revista Hospital Clínico Universidad de Chile, 2024)
The transition to Daylight Saving Time (DST) has been associated in the general population with various negative health effects, such as an increased risk of cardiovascular and cerebrovascular problems, along with symptoms of mental health issues. These effects are directly attributed to the sleep phase delay and, consequently, the deficit of sleep hours resulting from the measure. There is les evidence regarding the effect of DST on the child and adolescent population, although it is known that in these age groups, chronic sleep deprivation and disruption of chronobiological cycles play a role in the onset and course of various disorders, such as mood disorders, anxiety disorders, and neurodevelopmental disorders. The present work aims to review the existing evidence on the potential repercussions of DST on mental health in the adolescent population. First, a general model is presented regarding risk and protective factors for chronobiological cycles in adolescence. Subsequently, results from specific studies in adolescents are presented, covering both mental health and academic performance areas. Finally, the implications of these results are discussed.